2015
DOI: 10.1016/j.ifacol.2015.10.286
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory Control of Line Breakage for Thruster-Assisted Position Mooring System

Abstract: Thruster-assisted position mooring (TAPM) is an energy-efficient and reliable stationkeeping method for deep water structures. Mooring line breakage can significantly influence the control system, and ultimately reduce the reliability and safety during operation and production. Therefore, line break detection is a crucial issue for TAPM systems. Tension measurement units are useful tools to detect line failures. However, these units increase the building cost of the system, and in a large portion of existing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The significant wave height is 2.5 meters. The vessel moves around an equilibrium position by a PID-type DP controller (Ren et al, 2015a). The vessel is heading the waves while moored with 8 mooring cables evenly distributed with 45 deg intervals.…”
Section: Simulationmentioning
confidence: 99%
“…The significant wave height is 2.5 meters. The vessel moves around an equilibrium position by a PID-type DP controller (Ren et al, 2015a). The vessel is heading the waves while moored with 8 mooring cables evenly distributed with 45 deg intervals.…”
Section: Simulationmentioning
confidence: 99%
“…A methodology to detect line breakage and loss of of a buoyancy element in mooring lines was developed in Fang & 105 Blanke (2011); Blanke et al (2012) based on a structure-graph approach Blanke et al (2006). Detection of line breakage was studied in Ren et al (2015) using a supervisory control framework Hespanha (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Common to all of the above-mention methods, except for 110 Ren et al (2015), is the need for measuring the tension of mooring line forces which makes all these techniques susceptible to measurement noise or sensor failure. As a matter of fact, not all the mooring lines are equipped with loadcells and even when they are, it is frequently reported that loadcells do not work…”
Section: Introductionmentioning
confidence: 99%
“…Treated as a backup solution in abnormal conditions, this tension-based localization method can improve redundancy with only software updates. It is a companion paper to Ren et al (2015), which considers the problem of efficient linebreak detection in the case when tension sensors are not available in the TAPM system. Here we consider the converse case when tension sensors are available and can be used as redundancy to the posref systems.…”
Section: Introductionmentioning
confidence: 99%